Integrating diversity into therapy processes: the role of individual and cultural diversity competences in promoting equality of care - Moleiro, C.; Freire, J.; Pinto, N.; Roberto, S. (Counselling and Psychotherapy Research, 2018)
Background: One of the most significant challenges facing the provision of health care in present societies is the fact that the largest growing segment of the patient population is comprised of individual and culturally diverse people. However, the impact of this diversity on clinician–client interactions has only been examined recently. This study addresses the issues of culture and diversity in psychotherapy processes in Portugal. Methods: The study used an analogue experimental design, in a qualitative analogue study. The sample included 31 psychotherapists of varied years of experience and theoretical training background. Cultural diversity competences were measured with a semi-structured interview, through case conceptualisation and intervention planning by watching four minute video case vignettes with stigmatised group clients (varying on migration background, religion, race and sexual orientation), and all female college students presenting the same complaint. Two cases (of four) were presented to each psychotherapist (at random, controlling for presentation order). Interviews addressed case conceptualisation of each of the clients, as well as questions on how the participants typically integrated diversity in psychotherapy practice. Transcripts of the interviews were analysed incorporating features of thematic content analysis and Consensual Qualitative Research. Findings: Results showed that awareness, knowledge and skills were identified mostly at a level of blindness (n = 519; 70.5%) and precompetence (n = 172; 23.5%), while only a few units of analysis were categorised as competent (n = 43; 6.0%). Conclusions: This study highlights the importance of individual and cultural diversity competence training for clinicians, particularly in Europe, given its current migratory context, and encourages the promotion of diversity-sensitive approaches in mental health care.